Toothpastes for children and their detergent contents affect molecular mechanisms of odontogenesis in zebrafish embryos - ALTURFAN, EBRU IŞIK (My University, 2022)
We aimed to evaluate how different types of toothpaste (TP) for children affected molecular mechanisms of odontogenesis in zebrafish embryos. Commercially available TPs were selected according to their detergent contents as the cocamidopropyl betaine (CAPB) containing TP (TP1) and sodium lauryl sulfate (SLS) containing TP (TP2). TP3 contained no detergent. Effects of SLS, and CAPB alone were also examined. TP and detergent concentrations affecting development were determined as 750 mg/L and 4 mg/L, respectively. Embryos were exposed to TP1, TP2, TP3, SLS, CAPB, and embryo medium (control) for 72 h post fertilization. Acetylcholinesterase (AChE) activity and oxidant–antioxidant parameters were analyzed spectrophotometrically. Expressions of tooth development genes were evaluated by reverse transcription PCR (RT-PCR). Intraocular distance, lower jaw, and ceratohyal cartilage length were displayed using Alcian Blue staining.axin2andwnt10aexpressions increased in SLS and TP2 groups.igf2aandeve1expressions decreased in all groups except TP3.nrOb1expression decreased in TP1, SLS, and CAPB groups. Oxidant–antioxidant balance was disturbed in all groups except TP3, evidenced by increased lipid peroxidation, nitric oxide. SLS, and CAPB groups were more affected in terms of AChE, glutathione-S-transferase, and superoxide dismutase; perturbations were observed in cartilage structures. Altered expression of tooth development geneaxin2correlated withwnt10a, and with changes in cartilage structures in SLS and TP2 groups. TP3 group presented no disruptions in oxidant–antioxidant balance. Our study shows the availability of externally developing zebrafish embryos in examining the effects of TP’ contents on embryogenesis.
Keywords: Yaşam Bilimleri; Biyokimya; Moleküler Biyoloji ve Genetik; Temel Bilimler; Life Sciences; Biochemistry; Molecular Biology and Genetics; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Doğa Bilimleri Genel; Biyoloji ve Biyokimya; ÇOK DİSİPLİNLİ BİLİMLER; BİYOKİMYASAL ARAŞTIRMA YÖNTEMLERİ; Natural Sciences (SCI); Life Sciences (LIFE); NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; MULTIDISCIPLINARY SCIENCES; BIOCHEMICAL RESEARCH METHODS; Moleküler Biyoloji; Multidisipliner; Molecular Biology; Multidisciplinary